Quo Vadis Head of Local Government Authority: Products of Local Elections within the Principle of Decentralization - Luthfi Fahrul Rizal; Karina Puji Fauziah; Iqbal Reza Satria (UIN Sunan Gunung Djati, 2024)
Pattern by forming regional governments at the first level (provinces) and the second level (Districts/Cities). This is solely to achieve the optimization of national goals and development. However, the division of tasks and relationships between central and regional government authorities continues to experience dynamics. This issue needs to be deeply examined, specifically related to how to obtain and at what level of legitimacy strength, before determining how the working relationship and authority between the Central Government and the regions should be. This research employs a qualitative type, utilizing focused literature studies by taking relevant literature and legal provisions related to the position of regional leaders' authority in decentralization and provincial elections. The analysis used in this study applies the theory of the regional household system proposed by K. Tresna and Bagir Manan, the theory of the relationship model between the Central Government and regions by Clarke and Stewart, as well as the theory of people's sovereignty by John Locke, further emphasized by JJ Rosseau's social contract theory. The findings of this research assume that the methods and strengths of legitimacy regarding the people's sovereignty held by both the Central and regional governments are the same; the difference lies only in the scale of the election/governance areas. Local governments must have extensive autonomy and independence in conducting their regional governance affairs.